Phonological remediation program in students with developmental dyslexia - Salgado, Cíntia Alves; Capellini, Simone Aparecida [UNESP] (FapUNIFESP (SciELO), 2008)
Background: program for phonological remediation in developmental dyslexia. Aim: to verify the efficacy of a program for phonological remediation in students with developmental dyslexia. Specific goals of this study involved the comparison of the linguistic-cognitive performance of students with developmental dyslexia with that of students considered good readers; to compare the results obtained in pre and post-testing situations of students with dyslexia who were and were not submitted to the program; and to compare the results obtained with the phonological remediation program in students with developmental dyslexia to those obtained in good readers. Method: participants of this study were 24 students who were divided as follows: Group I (GI) was divided in two other groups - Gle with 6 students with developmental dyslexia who were submitted to the program; and Glc with 6 students with developmental dyslexia who were not submitted to the program; Group II (GII) was also divided in two other groups - GIIe with 6 good readers who were submitted to the program, and GIIc with 6 good readers who were not submitted to the program. The phonological remediation program (Gonzalez & Rosquete, 2002) was developed in three stages: pre-testing, training and post-testing. Results: results indicate that GI presented a lower performance in phonological skills, reading and writing when compared to GII in the pre-testing situation. However, GIe presented a similar performance to that of GII in the post-testing situation, indicating the effectiveness of the phonological remediation program in students with developmental dyslexia. Conclusion: this study made evident the effectiveness of the phonological remediation program in students with developmental dyslexia.
Keywords: Dyslexia; Intervention; Learning; Brazil; child; clinical trial; controlled clinical trial; controlled study; dyslexia; educational model; female; health care quality; human; language test; learning; linguistics; male; methodology; neuropsychological test; nonparametric test; phonation; physiology; psychological aspect; randomized controlled trial; reading; speech perception; standard; student; teaching; Child; Female; Humans; Language Tests; Linguistics; Male; Models, Educational; Neuropsychological Tests; Phonation; Program Evaluation; Reading; Remedial Teaching; Speech Perception; Statistics, Nonparametric; Students